2021
DOI: 10.1164/rccm.202007-2721oc
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus on the Tapering of Oral Corticosteroids for the Treatment of Asthma. A Delphi Study

Abstract: The study facilitator (C.M.S.) designed the study, developed the protocol and data collection tools, classified hundreds of raw brainstorming statements, organized survey logistics, collected and analyzed the data, and wrote the report. The steering committee (A.M.-G., D.P., E.R.B., G.W.C., M.G., and A.B.) provided initial recommendations of experts invited to enroll in the study and provided guidance to C.M.S. on study design, data collection, survey logistics, data analysis, and report writing. Expert panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 44 publications
4
91
0
16
Order By: Relevance
“…A schematic algorithm for tapering OCS was produced and is presented in Figure 3. 21 The European Respiratory Society/American Thoracic Society guideline on the management of severe asthma was also published. 25 The guideline authors conducted systematic reviews of the evidence to provide recommendations on the efficacy of mAb therapies, macrolide antibiotics and long-acting muscarinic agents.…”
Section: Asthma Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…A schematic algorithm for tapering OCS was produced and is presented in Figure 3. 21 The European Respiratory Society/American Thoracic Society guideline on the management of severe asthma was also published. 25 The guideline authors conducted systematic reviews of the evidence to provide recommendations on the efficacy of mAb therapies, macrolide antibiotics and long-acting muscarinic agents.…”
Section: Asthma Managementmentioning
confidence: 99%
“…This issue of OCS stewardship was certainly topical throughout 2020, with several publications addressing the use of OCS in asthma, the need to minimize their use and efficacious strategies to do so 18,21–24 . Suehs et al reported a modified Delphi survey which was conducted to develop expert consensus statements on the use of OCS, specifically relating to tapering of treatment, adverse effects, patient–physician shared decision‐making and adrenal insufficiency.…”
Section: Personalized Medicine In Severe Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Un panel de expertos consideró una dosis diaria de 5 mg o 500 mg anual aceptable o eventualmente una dosis de 10 mg con máximo 1 g anual. 50 No parece apropiado reducir o suspender el CSO en pacientes con granulomatosis eosinofílica con poliangeítis o con aspergilosis broncopulmonar alérgica, que recaen al reducirlo, en aquellos con intentos previos fallidos de destete de los CSO o en aquellos con insuficiencia suprarrenal. 50 El panel de expertos desarrolló un algoritmo de cómo se podría proceder con la reducción del CSO, con la velocidad de reducción dependiendo de la dosis de mantenimiento del CSO.…”
Section: Paciente Con Corticosteroide Oral De Mantenimiento: Cuándo Y Cómo Destetarunclassified
“…Se puede encontrar en la publicación original y en el anexo 7. 50 Damos una sugerencia de cómo llevar el abordaje, siempre individualizando: progresivamente. III.…”
Section: Paciente Con Corticosteroide Oral De Mantenimiento: Cuándo Y Cómo Destetarunclassified